2013
DOI: 10.1021/es403377p
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Silver Nanoparticles in a Model of Pulmonary Surfactant

Abstract: The growing use of silver nanoparticles (AgNPs) in consumer products has raised concerns about their potential impact on the environment and human health. Whether AgNPs dissolve and release Ag+ ions, or coarsen to form large aggregates, is critical in determining their potential toxicity. In this work, the stability of AgNPs in dipalmitoylphosphatidylcholine (DPPC), the major component of pulmonary surfactant, was investigated as a function of pH. Spherical, citrate-capped AgNPs with average diameters of 14 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
123
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 68 publications
9
123
0
1
Order By: Relevance
“…Surfactant components are known to opsonize bacteria and may also bind to inhaled particles 4042 and thus affect how a cell recognizes and interacts with a nanoparticle. To investigate this, we preincubated nanoparticles with human lung lining liquid (collected via bronchoalveolar lavage) for 30 min prior to cell exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Surfactant components are known to opsonize bacteria and may also bind to inhaled particles 4042 and thus affect how a cell recognizes and interacts with a nanoparticle. To investigate this, we preincubated nanoparticles with human lung lining liquid (collected via bronchoalveolar lavage) for 30 min prior to cell exposure.…”
Section: Resultsmentioning
confidence: 99%
“…12,28,29 The confounding influences of these factors can make it difficult to compare dissolution data and biological impacts 30 reported in the literature as a) Electronic mail: don.baer@pnnl.gov demonstrated by the wide variation in the amounts of Ag observed to dissolve during in-vitro studies with a range of seemingly inconsistent biological impacts. 6,25,[31][32][33][34][35][36][37] After testing several AgNPs, Matzke et al 18 found no clear relationship between toxicity and different particle shapes, sizes, or coatings. 18 They suggest an "intricate interplay between particle characteristics and the media in which the tests are carried out."…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted investigating the dissolution of Ag ENPs in artificial body fluids such as fluids representing the environment of the stomach, blood and airways (Stebounova et al, 2011a;Leo et al, 2013). Leo et al (2013) studied the effect of a model pulmonary surfactant on Ag ENPs, and showed a decrease in the kinetics of Ag ENP dissolution and of their aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Leo et al (2013) studied the effect of a model pulmonary surfactant on Ag ENPs, and showed a decrease in the kinetics of Ag ENP dissolution and of their aggregation. Although there are published data on Ag localization and speciation in plants exposed to Ag ENPs (Larue et al, 2014), equivalent data on animal cells and tissues after Ag ENP exposure is lacking.…”
Section: Introductionmentioning
confidence: 99%